Work-Life Balance and Job Stress of Employees of a Lone Agricultural College in Bulacan, Philippines - Esguerra, Imee De Guzman (Institut Pariwisata dan Bisnis Internasional, 2020)
This study utilized the descriptive correlational research method wherein a modified survey questionnaire was used to gather data from 107 employees of BASC. Frequency count, percentage, Pearson's r Correlation Coefficient was used in data analysis. The majority of the respondents are female, married, with below five-year work experience and rank and file employees. The total work-life balance of the majority of the respondents was out of balance as more than half of them felt that their work-life balance in terms of work and career, friends and family, fitness and health, fun/recreation and money is on the edge while the rest is out of balance. Only in terms of romance and significant other did they believe that they have a right balance work-life situation. Among the demographic profile, age, educational attainment, and work-life balance in all the seven areas were found to be significantly correlated to the job stress of the employees in BASC.